Role of Eros, a novel transmembrane protein, in regulation of host defence. (25th February 2016) - Thomas, David C; Clare, Simon; Sowerby, John M; Pardo, Mercedes; Juss, Jatinder K; Goulding, David A; Van der Weyden, Louise; Storisteanu, Daniel M L; Prakash, Ananth; Espeli, Marion; Flint, Shaun; Lee, James C; et al.
Abstract: Background: Reactive oxygen species (ROS), generated via the phagocyte NADPH oxidase cytochrome b558, are essential for effective immune responses to common and serious pathogens. The phagocyte NADPH oxidase is a multisubunit protein complex and deficiency of either the membrane bound or cytoplasmic components leads to chronic granulomatous disease, a serious and often fatal illness characterised by recurrent infections and autoimmunity. Moreover, abnormal generation of ROS has been implicated in the pathogenesis of multigenic autoimmune diseases such as systemic lupus erythematosus. Eros (essential for reactive oxygen species), encoded by bc017643, is a novel transmembrane protein that is highly expressed in the immune system and highly conserved in evolution but has no previously identified function. Eros is an orthologue of the plant protein Ycf4, necessary for expression of proteins of the photosynthetic photosystem 1 complex, an NADPH oxio-reductase complex. We elucidated its role in infection in mice. Methods: ROS are essential for host defence against the serious bacterial pathogen Salmonella enterica serovar Typhimurium. We screened individual knockout mice (Wellcome Trust Knockout mouse project) for susceptibility to salmonella infection. Having identified mice deficient in Eros as being highly susceptible to salmonella, we used ex-vivo approaches including reactive oxygen burst assays and western blot, to characterise their defect further. Findings: We found that Eros was essential for host defence to infection. Eros was crucial for generating reactive oxygen species through regulation of the essential NADPH oxidase components, gp91 and p22. Eros-deficient mice expressed almost no gp91 and p22 in neutrophils and macrophages secondary to accelerated degradation in the absence of Eros. As a result Eros-deficient mice died rapidly after infection with salmonella or listeria. Eros also regulated the ROS-dependent formation of neutrophil extracellular traps and melanoma metastases. Interpretation: We have found a a key role for Eros in regulating host defence. The finding that Eros-deficient mice lack gp91 and p22 at the protein, though not mRNA, level shows how these key components of the reatcive oxygen burst are protected from degradation and furthers our understanding of reactive oxygen burst biology. Eros is highly conserved between mouse and man so it is likely that it also has a crucial role in human immunity. Funding: Wellcome Trust, Academy of Medical Sciences starter grant.